An Explorative Study of Bima City Public Perception of the Risks of Smoking on the Health of Mothers and Children in Bima City - Zahratul Hayati; Nurul Qamarya; Puput Artika June; Jelita Purnama Sari (Jurnal EduHealth, 2026)
Statistics Indonesia Exposure to cigarette smoke in pregnant women is correlated with an increased risk of low birth weight and child morbidity; evidence from the last 5 years in Indonesia also links household cigarette smoke exposure to the risk of stunting. Smoking remains a serious public health problem, especially in developing countries like Indonesia. Exposure to cigarette smoke not only impacts active smokers, but also vulnerable groups, including pregnant women, breastfeeding mothers, and children. The study used a qualitative-exploratory design with in-depth interviews and Focus Group Discussions (FGDs). Informants were selected using purposive-maximum variation, including pregnant and breastfeeding mothers, husbands/family members of smokers, adolescents, health cadres, and religious and community leaders in six sub-districts in Bima City. The number of informants was 45 people, consisting of 21 in-depth interviews and 4 FGDs. The results showed that most people are aware of the dangers of smoking in general, but the perception of the risks to mothers and children is still low. Social norms, patriarchal culture, and the assumption that smoking is an individual right are the main factors influencing high exposure to cigarette smoke in households. The implementation of Bima Mayoral Regulation Number 15 of 2023 concerning Smoke-Free Areas (KTR) is considered positive, but has not been effective at the household level.